Climate Change Projections for the Australian Monsoon From CMIP6 Models. Issue 13 (28th June 2020) - Narsey, S. Y.; Brown, J. R.; Colman, R. A.; Delage, F.; Power, S. B.; Moise, A. F.; Zhang, H.
Abstract: Climate change projections for the Australian monsoon have been highly uncertain in previous generations of coupled climate models. The new Coupled Model Intercomparison Project Phase 6 (CMIP6) ensemble provides an opportunity to address the uncertainty in future projections for northern Australia. We find that the range in Australian monsoon projections from the available CMIP6 ensemble is substantially reduced compared to CMIP5, although models continue to disagree on the magnitude and direction of change. While previous CMIP5 studies identified warming in the western equatorial Pacific as important for Australian monsoon projections, here we show that the western Pacific is not strongly connected to northern Australian precipitation changes in the CMIP6 models. By comparing groups of models based on their future projections, we note that the model‐to‐model differences in Australian monsoon projections are congruent with the zonally averaged precipitation response in the Southern Hemisphere tropics within each model. Key Points: Australian monsoon changes are smaller in the available CMIP6 ensemble than the CMIP5 ensemble CMIP6 models still disagree on changes to Australian monsoon precipitation in a warmer world Australian monsoon changes are congruent with the zonal mean precipitation change, more evident in CMIP6 than CMIP5